Shooting Galleries, Ordinances of the City Council of Memphis, Ch. 4, Art. 5, §§1-8 (1867). - (:unkn) unknown (General Publisher, 1867)
That from and after the passage of this ordinance, no person or persons shall be allowed, under any pretence whatever, to open, set up or establish a shooting gallery in the first story of any building within the corporate limits of the City of Memphis, under a penalty of fifty dollars per day for each and every day that such shooting gallery shall be set up or continued within said corporate limits of the city.
--
Keywords: SHOOTING RANGES OR GALLERIES